Are Regional Differences in Utility Eliminated over Time? Evidence from Germany - David Maddison; Katrin Rehdanz (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Hedonic theory assumes that changes in land prices and wage rates eliminate the utility advantages of differing locations. Using happiness data from the German socio-economic panel this paper empirically tests whether regional utility differences exist and if so whether utility levels show any tendency to converge over time. Empirical analysis reveals substantial differences in utility over different regions of Germany. Analysing a panel of data indicates that even if individual utility levels are at any one moment in disequilibrium they are rapidly converging over Germany for all types of individuals.
Keywords: 330; Convergence; Hedonic Analysis; Happiness; Migration; Germany